MAKSIM KEARIFAN DALAM TUTURAN DIREKTIF PEREMPUAN JEPANG DAN PADANANNYA DALAM BAHASA INDONESIA - Nani Sunarni (Jurnal Sastra - Studi Ilmiah Sastra, 2020)
The process of communication as a process of social interaction requires regularity corresponding to the patterns of behavior that apply in the language community. For the creation of a smooth communication to maintain a lasting peace, the Japanese people are very strong to hold the principles of cooperation. For example utterances ohanashi ga arimasu (something wants to talk about). The speech in terms of structure is an assertive illocutionary act. However, the speech may be a directive illocutionary act when spoken in the context of the request even though no markers directive. It aims to maintain harmony between speaker and hearer. To establish effective communication, it becomes important to investigate. Therefore, this study aimed at how to use the principles of interpersonal action directive illocutionary counterpart in the Japanese and Indonesian. The method used in this research is descriptive qualitative method. Data used in the form of speech acts in Japanese demand that comes from the Japanese-language drama. To analyze the data used in the view of the theory of pragmatics Leech (1993). Based on the analysis, it was identified that there is a gradation in action directive illocutionary Japanese. This study is theoretically beneficial to add a reference about pragmatics. In practical terms, the results of this study can be used as a base for Japanese language teaching materials.